Gender dalam Perspektif Dosen Pendidikan Agama Islam Institut Agama Islam Tribakti Kediri - Maula, Lia Ni'matul; Fajar, Abbas Sofwan Matlail (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat (LP3M) UIT Lirboyo Kediri, 2022)
Gender in terms of religion, law, or social order has been widely discussed in academic circles. There are Islamic boarding schools that have higher education institutions that must maintain the classic pesantren culture, but on the other hand, must implement co-education (co-education). Such as IAIT Lirboyo Kediri, KH University. Hasyim Asy'ari Jombang, and so on. An in-depth study of women from the pesantren and academic perspective is very interesting to study. Women's identity and identity can be highlighted in the legal aspect as well as social order based on classical Islamic literature which is not only understood textually. This research is qualitative research with the type of phenomenological research. Data collection techniques using in-depth interviews and documentation. Meanwhile, data analysis uses data reduction, data presentation, and verification. The results of the study, namely: (1) IAIT Kediri campus regulations in the form of unification of space between students and female students so that discussions are more active, academic dress code so that students and students can position themselves according to where they are, maintain Islamic ethics on campus as well as in discussions with the opposite sex when in the classroom or on campus. (2) The perspective of Tribakti lecturers on gender in the form of gender equality regarding the right to knowledge and equality of dignity is proven that women can also become leaders in organizations.